Penguatan Kesadaran Hukum Warga Muda terhadap Tindak Pidana Kekerasan Seksual Berbasis Elektronik Berdasarkan UU TPKS: (Studi Pengabdian Masyarakat di Desa Molowahu, Kecamatan Tibawa) - Imran, Suwitno Yutye; Lisnawaty W. Badu; Nurvazria Achir; Yahya, Agung Prayuda; Janwar Hippy (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
The rapid advancement of information technology has triggered an escalation in Electronic-Based Sexual Violence (KSBE), threatening the safety of young people in cyberspace. The community service activity serving as the focus of this study was conducted in Molowahu Village, Tibawa District, Gorontalo Regency, where such vulnerability was exacerbated by low legal awareness and the limitations of pre-existing regulations—prior to the enactment of Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS)—which often led to the secondary victimization (or "double criminalization") of victims. This study aims to analyze the legal reconstruction of KSBE handling under Law No. 12 of 2022 (UU TPKS) and to formulate a doctrinal strategy—implemented in Molowahu Village—to strengthen legal awareness among young people. A normative legal research method was employed, utilizing both statutory and conceptual approaches. The findings indicate that Article 14 of the UU TPKS introduces a juridical re-conceptualization, positioning KSBE as a distinct criminal offense based on the absence of consent, while simultaneously dismantling the moralistic stigma inherent in previous regulations. Implementation in Molowahu Village demonstrates that strengthening legal awareness among young people requires a transformation from mere legal knowledge to the institutionalization of an empathetic legal culture, an understanding of victims' rights to recovery, and proficiency in digital privacy protection literacy—all achieved through active collaboration among academics, university students, village officials, and local customary leaders.